Understanding the Lessons of Failure Public Policy over the Pandemic Issues in Global Context - Zuchri Abdussamad; Ani Heryani; Vani Wirawan; Ade Iskandar; Nur Arif Nugraha (Budapest International Research and Critics University, 2021)
This paper wanted to understand how the lessons learned from the failure of public policies in responding to the Pandemic in a global context. The success of responding to a pandemic that has become the task of public office holders is closely related to implementing public policies. For this reason, we tried to examine several international publications published after the global hit pandemic. This study uses secondary data that we find through an electronic search that we specialize in the latest issue between 2017 and 2021. Then we examine it with a phenomenological approach such as a data coding system, evaluation, and in-depth interpretation to get valid and reliable finding data. So based on the findings and discussion data, we can conclude that there are several lessons that we can take from the failure of pandemic policies in the global context. Among other things, lessons on humanitarian commitment, lack of natural resources, lousy application behavior, corruption, and several other bureaucratic mistakes. Thus, these findings can add insight to the parties.